Dulaglutide Alleviates LPS-Induced Injury in Cardiomyocytes - Wang, Rijun; Wang, Ning; Han, Yuping; Xu, Jiyao; Xu, Zesheng (ACS omega, 2021)
Background and purpose: Sepsis is a severe infection-induced disease with multiple organ failure, and sepsis-induced cardiomyopathy is a fatal condition. Inflammatory response and oxidative stress are reported to be involved in the development of sepsis-induced cardiomyopathy. Dulaglutide is a novel antidiabetic agent that is currently reported to exert an anti-inflammatory effect. The present study aims to explore the potential protective property of dulaglutide on lipopolysaccharide (LPS)-induced injury on cardiomyocytes. Methods: LPS was used to induce an in vitro injury model on cardiomyocytes. The mitochondrial reactive oxygen species (ROS) level was detected using MitoSOX red, and reduced glutathione (GSH) was measured to evaluate the status of oxidative stress in H9c2 myocardial cells. The expressions of NADPH oxidase-1 (NOX-1) and inducible nitric oxidesynthase (iNOS) were determined using real-time PCR and western blot analysis. Real-time PCR and enzyme-linked immunosorbent assay (ELISA) were both used to detect the expressions and concentrations of tumor necrosis factor-α, interleukin-1β, interleukin-17, matrix metalloproteinase-2, and matrix metalloproteinase-9 in H9c2 myocardial cells, respectively. The production of nitric oxide (NO) was measured using the Griess reagent. The levels of creatine kinase isoenzyme-MB (CK-MB) and cardiac troponin I (cTnI) were detected using ELISA. Western blot was utilized to determine the expressions of toll-like receptor 4 (TLR4), myeloid differentiation factor 88 (MyD88), and p-NF-κB p65 in H9c2 myocardial cells in the nucleus. Results: First, dulaglutide ameliorated LPS-induced oxidative stress by suppressing the production of mitochondrial ROS and elevating the level of reduced GSH, as well as downregulating NOX-1. Second, the LPS-induced cardiomyocyte injury was alleviated by dulaglutide through downregulating CK-MB and cTnI, accompanied by inhibiting iNOS expression and NO production. Lastly, the production of inflammatory factors and upregulation of MMPs induced by LPS were both significantly reversed by dulaglutide through suppressing the TLR4/Myd88/NF-κB signaling pathway. Conclusions: Dulaglutide alleviated LPS-induced injury in cardiomyocytes by inhibiting inflammation and oxidative stress.